Evaluating the Cost of Quality in the Furniture Factory - Othman, Ahmad Fauzi (2001)
The study was carried out in a furniture factory, which specialises in manufacturing of bedroom, and dining set furniture for export market. The purpose of this study was to identify the quality cost and to provide guidance to general management and quality program management to enable them to structure and manage programs to assist in the overall product cost reduction. The cost of quality was divided into four groups, which were prevention cost, appraisal cost, internal failure cost and external failure cost. The prevention cost was 30.2%, appraisal cost was 17.6%, internal failure cost was 43% and external failure cost was 9%. The major contributor internal failure cost was from down grading cost, valued at RM 30,000, The main contribution from prevention cost was quality planning around Rm 30,000. Receiving inspection gave a higher value in appraisal cost , which was RM 13,800 and the external cost just contributed only RM 10,000. Warranty claim was the most highest cost, it came from the department of Replacement Part or RP. From the result it showed that typical ratio for TOC as a percentage of sales was 15%, value added was 37% and direct labor cost was 2.7%. The value of direct labour cost was below 5% (international standard). This showed that this company has an efficient quality program and well trained staff to fulfill the quality requirements.